Niveles de inmunoglobulina E en relación con el cuadro clínico de los pacientes asmáticos - Castro Jiménez, María Dolores (2015)
People are not born with allergies in fact it is the genetic predisposition and factors that make the person allergic to certain allergens. Among the most common allergic diseases is asthma, which affects 10% of the child population and 5% of the adult population. (1) In this work it was proposed to quantify the immunoglobulin E (IgE). Another goal was to establish the degree of severity and lastly to relate the clinical picture with the IgE values obtained in asthmatic patients; using a descriptive, retrospective and cross-sectional study, comprising 250 patients attending the ‘Abendaño’ outpatient clinic and the sample consisted of 105 asthmatic patients who met the inclusion criteria. The electrochemiluminescence technique was used to determine the IgE level, and the clinical history of the patients was used to find out the degree of severity. It was determined that from the 105 asthmatic patients, 87% had different immunoglobulin values. According to the review of those patients’ medical records; 34% (36 patients) had moderate persistent asthma, 30% (31 patients) had mild persistent asthma, 26% (27 patients) had severe persistent asthma and 10% (11 patients) had intermittent asthma. Finally the altered IgE levels were linked to the clinical picture of patients and it was found that 36% (38) were patients with moderate persistent asthma, 24% (25) with severe persistent asthma, 13% (14) with mild persistent asthma and 10% (10) with intermittent asthma.It is important to consider that the doctors who treat asthma patients when the value of IgE is found altered carry out more specific tests such as the analysis of specific IgE antibodies to allergens for the treatment to work well and those way patients can take measures to prevent the deterioration of their health. KEYWORDS: Asthma, Allergy, IgE and Population.